ISLAMIC EDUCATION AND THE SOCIETY ERA 5.0 (Opportunities and Challenges on Islamic Education Institutions) - Irfan Setia Permana; Naomi Ainun Hasanah (Postgraduate Program Magister Pendidikan Agama Islam, 2025)
Determination of the globalization era is marked by Society Era 5.0 as the result of Industrial Revolution 4.0. One of the impacted elements of this is education institutions. The presence of technology is somewhat at its peak of rapid development and thus demands the education institution to adapt to the digitalization including islamic education. Therefore, a right solution to face Society Era 5.0 is required. Society living in this era is highlighted by those who mastered science and technology. Method applied in this research is library research with a qualitative approach. According to observation results, there are some problems found that actually lead to opportunities and challenges in Islamic Education. The opportunity is improving the quality of human resources for the educators. Moreover, Society Era 5.0 can be a marketing media to the development of Islamic Institution. It will also provide space for revitalization towards the modernism paradigm as well as optimalizatin on institution fundings. Besides the opportunities, there will be challenges such as the awareness of most islamic educators on science and technology, optimization of teacher standards, efforts in initiating nondicotomic paradigm and also determining strategies used to push Islamic Education as the primary center of science and technology.